Sulfated Extract of Abelmoschus Esculentus: A Potential Cancer Chemo-preventive Agent - Gamal-Eldeen, Amira M.; Amer, Hassan; Fahmy, Cinderella A.; Dahlawi, Haytham; Salman, Asma; Raafat, Bassem M. (Current Pharmaceutical Biotechnology, 2022)
Background: Abelmoschus esculentus (AE) (okra), is an edible plant used in many food applications. Objective: This study explored whether sulfated AE (SAE) has promising cancer chemopreventive activities that may recommend it as a functional food supplement instead of (or in addition to) AE for the population at risk of cancer and in the health food industry. Methods: Cytochrome P450-1A (CYP1A) was estimated by fluorescence enzymatic reaction, using β-naphthoflavone-treated cells (CYP1A inducer). Peroxyl and hydroxyl radical scavenging was assayed by oxygen radical absorbance capacity assay. Flow cytometry was used to analyze apoptosis/necrosis in MCF-7 cells, cell cycle phases in MCF-7 cells, and macrophage binding to fluorescein isothiocyanate-lipopolysaccharide (FITC-LPS). Nitric oxide was determined by Griess assay in LPS-stimulated macrophages, and cytotoxicity was determined by MTT assay. Diethylnitrosamine (DEN) was used to induce hepatic tumor initiation in rats. Placental glutathione-S-transferase (GSTP; an initiation marker) was stained in a fluorescence immunohistochemical analysis of liver sections, and histopathological changes were examined. Results: SAE exhibited strong antitumor initiation and antitumor promotion activities. It suppressed CYP1A, scavenged peroxyl and hydroxyl radicals, induced macrophage proliferation, suppressed macrophage binding to FITC-LPS, inhibited nitric oxide generation, showed specific cytotoxicity to human breast MCF-7 adenocarcinoma cells, and disturbed the cell cycle phases (S and G2/M phases) in association with an increased percentage of apoptotic/necrotic MCF-7 cells. Over a short time period, DEN stimulated liver cancer initiation, but SAE treatment reduced the DEN-induced histopathological alterations and inhibited CYP1A and GSTP. Conclusion: SAE extract has the potential for use as an alternative to AE in health foods to provide cancer chemoprevention in populations at risk for cancer.
Keywords: cancer chemoprevention